Geologic context and potential EVA targets at the lunar south pole - Gawronska, Aleksandra; Barrett, Natasha; Boazman, Sarah; Gilmour, Cosette; Halim, Samuel; Harish; McCanaan, Kathryn; Satyakumar, Animireddi V.; Shah, Jahnavi; Meyer, Heather M.; Kring, David A. (David Allen); orcid:0000-0002-6888-9868; et al. (Advances in Space Research, 2020)
The Artemis human landing system concept of operations is initially limited to two astronauts who land "on the lunar south pole" and will not exceed a surface stay of 6.5 days near the south pole (NASA, 2019a). Potentially, five extravehicular activities (EVAs) are possible in that interval (NASA, 2019b). Landing, traverses by crew and supporting robotic assets, and targeted sampling of the region require pre-mission geologic assessments of the lunar south pole. Here, we provide an initial geologic assessment of the lunar south pole, Shackleton crater, and the geology that may be accessible in that type of short duration surface stay.